Kampanye Keselamatan Penerbangan (Aviation Safety) bagi Siswa SMA/SMK di Jayapura - Nugrahayani, Tiara; Biringkanae, Pipa; Makanuay, Nikolas; Kona, Musri; Bunahri, Rifqi Raza (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2024)
Economic growth and increased global connectivity have been greatly aided by the aviation sector. Very important items are usually sent via air transportation. However, with these changes come important issues for aviation safety, especially in the airport environment. Security and safety are important components that require the cooperation of all related parties. Areas around airports, which are often inhabited by highly diverse communities, are critical to aviation security. In these circumstances, careful action and planning are required to reduce the risk of accidents and incidents that endanger flight crew, local communities and infrastructure. This research uses a literature review. Bibliographic research / literature research, is a type of research that examines or critically reviews knowledge, concepts, or findings found in academically oriented literature, as well as explaining how that literature makes theoretical and methodological contributions to a particular topic. The results of this aviation safety campaign showed that 44 participants who participated in aviation safety training experienced an increase in scores, while 11 participants did not experience an increase. This campaign aims to increase the knowledge and understanding of participants related to air traffic services, human factors, and safety, especially high school / vocational aviation students. It is expected that the graduates can use it when working in the aviation industry because safety is very important.